2013
DOI: 10.1068/p7476
|View full text |Cite
|
Sign up to set email alerts
|

Retention of Gap Length in Normal-Hearing Listeners

Abstract: Listener retention of silent, gap-length duration was studied. Just noticeable differences (JNDs) for gap length within standard and comparison stimuli were obtained for intervals with and without intervening noise bursts, including a condition with gapped intervening bursts. Outcomes indicate that gap duration itself can be determinant. Also, JNDs were similar whether intervening stimuli were present or absent, differing from results reported for pitch, loudness, and timbre retention. The latter suggests addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Although not specifically tested here, the perceived context of the silent gap may influence whether the retroactive interference occurs for retention of such acoustic events. Ries et al (2013) found that retention of gap length between sound events demonstrates no significant interference from interpolated sound sequences. Conversely, Deutsch (1986) reported that retention interference occurs when sound durations are measured using marked empty intervals.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Although not specifically tested here, the perceived context of the silent gap may influence whether the retroactive interference occurs for retention of such acoustic events. Ries et al (2013) found that retention of gap length between sound events demonstrates no significant interference from interpolated sound sequences. Conversely, Deutsch (1986) reported that retention interference occurs when sound durations are measured using marked empty intervals.…”
Section: Discussionmentioning
confidence: 95%
“…Sound event duration is one acoustic attribute that conveys useful information for human (eg Kingston, Kawahara, Chambless, Mash, & Brenner-Alsop, 2009;Monaghan, White, & Merkx, 2013) and beast (eg Gerhardt & Doherty, 1988;Narins & Capranica, 1978;Nelson, 1988). Retention of some temporal acoustic information (ie silent gap length between stimuli) is resistant to interference from subsequently presented auditory stimuli (Ries, Woods, & Smith, 2013). However, retention of stimulus event duration defined by marked empty intervals (ie acoustic signals mark the onset and offset of a sound with silence in between) does not exhibit such resistance in the presence of similar, interpolated sounds presented in a simple metronomic manner (Deutsch, 1986).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation